Molecular Research for Cereal Grain Quality (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents 13 papers published in the Special Issue entitled "Molecular Research for Cereal Grain Quality" of the International Journal of Molecular Sciences, together with an editorial. All of these papers provide new scientific insights into molecular research for cereal grain quality, with most studies focusing on the grain quality of rice and wheat crops. More papers with a broader coverage of the grain quality features of different cereal crops need to be collected in future Special Issues.